Characteristics of incident substance-induced psychosis compared to first-episode psychotic disorders: A nationwide register-linkage study from Sweden - Jeyapalan, Jeyaniroshan (Elsevier, 2025)
Background
There is no previous research comparing preceding characteristics between incident substance-induced psychosis (SIP) and first-episode psychotic disorders (FEPD).
Aims
To compare work-related factors and psychiatric morbidity preceding the incident psychotic episode between persons with SIP to persons with FEPD (ICD-10 F20–F29).
Methods
Incident SIP aged 16–65 years (n = 7320, 79.4 % male) were identified from the Swedish National Patient Register (NPR) during the years 2006–2016, matched 1:1 (age, sex, year) with FEPD. Information on work-related factors and preceding psychiatric morbidity was collected from national registers. Comparisons between SIP vs FEPD were made using logistic regression analysis, adjusted (aOR) with education level, family situation, living area, country of origin, and Charlson Comorbidity Index.
Results
Previous self-harm (22.9 % vs 11.3 %; aOR 2.4, 95%CI 2.2–2.6), ADHD (14.4 % vs 8.9 %; aOR 1.8, 95%CI 1.6–2.0), and SUD (68.3 % vs 22.3 %; aOR 7.2, 95%CI 6.6–7.9) were more prevalent among SIP, while all other psychiatric disorders were less common compared to FEPD. Also, persons with SIP were more often unemployed (24.6 % vs 18.6 %; aOR 1.2, 95%CI 1.1–1.3), had less any income from work (29.3 % vs 31.1 %; aOR 0.9, 95%CI 0.8–0.98), but were also less often on a sickness absence (8.6 % vs 9.9 %; aOR 0.8, 95%CI 0.7–0.95) or on a disability pension (18.6 % vs 26.3 %; aOR 0.6, 95%CI 0.5–0.7) compared to FEPD.
Conclusions
Persons with SIP have less premorbid psychiatric morbidity than those with FEPD, apart from self-harm, ADHD, and SUD. Also, there is a higher likelihood of labour market marginalisation among persons with incident SIP than persons FEPD.